Intertextuality of Suicide Phenomena and the Myth of Pulung Gantung in Gunungkidul, Yogyakarta, in the Short Film Lamun Sumelang - Deby Christi (LITERA : Jurnal Bahasa Dan Sastra, 2026)
This study aims to reveal the form of intertextuality between the short film Lamun Sumelang (2019) by Ludy Oji Prastama and the creative work Pulung Gantung: Menyingkap Tragedi Bunuh Diri di Gunungkidul (Pulung Gantung: Uncovering the Tragedy of Suicide in Gunungkidul) (2002) by Darmaningtyas by examining the interconnected meanings, themes, and socio-cultural representations presented in both works. The phenomenon of suicide, which frequently occurs in Gunungkidul, Yogyakarta Special Region, has long been a complex social and cultural issue. Although various studies indicate that the main factors contributing to suicide in the region are related to socio-economic pressure, poverty, shame (wirang), and social isolation, most of the community still associates it with the myth of pulung gantung—a reddish celestial light believed to be a sign foretelling death by hanging. A descriptive qualitative analysis is employed using Fitzsimmons (2013) theory of intertextuality and the mise-en-scène approach as a supporting framework for visual analysis in film. The study concludes that Lamun Sumelang represents a reinterpretation and revitalization of the text Pulung Gantung through the medium of cinema presenting an intertextual dialogue between social reality, local myth, and contemporary artistic expression. Through the lens of intertextuality, the film functions not only as a cultural representation but also as an educational and reflective medium for understanding the phenomenon of suicide within rural Indonesian society.